Analysis of Business Strategy, Market Orientation and Innovation Capability On Competitive Advantage Through PT Abc's Firm Performance - Rio Gahari (Publikasi Indonesia, 2024)
Companies today are increasingly recognizing the importance of adopting business and innovation strategies to stay competitive in an ever-changing marketplace. This study aims to examine the relationship between business strategy, market orientation, innovation capabilities, company performance, and competitive advantage in the context of PT ABC, a construction and public procurement company established in 2018. The research method used is quantitative, with preliminary stages, observation, filling out questionnaires, data collection, data processing, and validity tests. Data is obtained through surveys and analyzed to examine the effect of these variables on the company's competitive advantage. The results showed that business strategy has a positive effect on the company's innovation capabilities and performance. Market orientation also has a positive effect on company performance. However, market orientation does not have a significant effect on innovation capabilities, and innovation capabilities have no effect on competitive advantage. These findings provide important insights for PT ABC and other companies in developing business strategies, strengthening market orientation, and enhancing innovation capabilities to achieve competitive advantage in competitive markets.